Partial and Transient Clinical Response to Omalizumab in IL-21-Induced Low STAT3-Phosphorylation on Hyper-IgE Syndrome. (4th July 2019) - Alonso-Bello, Cesar Daniel; Jiménez-Martínez, María del Carmen; Vargas-Camaño, María Eugenia; Hierro-Orozco, Sagrario; Ynga-Durand, Mario Alberto; Berrón-Ruiz, Laura; Alcántara-Montiel, Julio César; Santos-Argumedo, Leopoldo; Herrera-Sánchez, Diana Andrea; Lozano-Patiño, Fernando; Castrejón-Vázquez, María Isabel
Abstract : Hyper-IgE syndrome (HIES) is a rare primary immunodeficiency characterized by elevated levels of immunoglobulin E (IgE), eczematous dermatitis, cold abscesses, and recurrent infections of the lung and skin caused by Staphylococcus aureus . The dominant form is characterized by nonimmunologic features including skeletal, connective tissue, and pulmonary abnormalities in addition to recurrent infections and eczema. Omalizumab is a humanized recombinant monoclonal antibody against IgE. Several studies reported clinical improvement with omalizumab in patients with severe atopic eczema with high serum IgE level. We present the case of a 37-year-old male with HIES and cutaneous manifestations, treated with humanized recombinant monoclonal antibodies efalizumab and omalizumab. After therapy for 4 years, we observed diminished eczema and serum IgE levels.